2016
DOI: 10.1371/journal.pone.0156309
|View full text |Cite
|
Sign up to set email alerts
|

Population-Based Assessment of Hypertension Epidemiology and Risk Factors among HIV-Positive and General Populations in Rural Uganda

Abstract: BackgroundAntiretroviral therapy scale-up in Sub-Saharan Africa has created a growing, aging HIV-positive population at risk for non-communicable diseases such as hypertension. However, the prevalence and risk factors for hypertension in this population remain incompletely understood.MethodsWe measured blood pressure and collected demographic data on over 65,000 adults attending multi-disease community health campaigns in 20 rural Ugandan communities (SEARCH Study: NCT01864603). Our objectives were to determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
81
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(107 citation statements)
references
References 50 publications
22
81
4
Order By: Relevance
“…Our findings are consistent with previous reports of CVD risk factor prevalence among ART‐experienced PWH in South Africa: hypertension (12% to 39%) ; Stage 2 hypertension (14% to 66%) ; impaired glucose tolerance (16% to 21%) ; diabetes (2% to 8%) ; and self‐reported tobacco smoking (1% to 31%) . This substantial prevalence of CVD risk factors among a patient population who attends clinic on a routine basis underscores an important opportunity to screen for these intervenable risk factors.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings are consistent with previous reports of CVD risk factor prevalence among ART‐experienced PWH in South Africa: hypertension (12% to 39%) ; Stage 2 hypertension (14% to 66%) ; impaired glucose tolerance (16% to 21%) ; diabetes (2% to 8%) ; and self‐reported tobacco smoking (1% to 31%) . This substantial prevalence of CVD risk factors among a patient population who attends clinic on a routine basis underscores an important opportunity to screen for these intervenable risk factors.…”
Section: Discussionsupporting
confidence: 91%
“…Among participating participants in this study, 42% were aware of a past diagnosis of hypertension, of whom 51% were on treatment; however, only 17% of patients prescribed antihypertensives had blood pressures in normal range. Data from Uganda and Tanzania demonstrate the same leaky care cascade: only 20% to 25% of patients with hypertension who attended HIV clinics were already aware of their diagnosis, and only 14% were on treatment with roughly half under control . In our study population, 50% of participants who met criteria for diabetes were already diagnosed and 85% were on treatment with 36% in control; these findings are similar to those reported from South Africa regarding the diabetes care cascade among the participants not living with HIV (40% diagnosed; 94% on treatment; 51% in control) .…”
Section: Discussionsupporting
confidence: 83%
“…Although we document increasing blood pressure after ART initiation, our finding should be taken in light of population-based surveys from sub-Saharan Africa, which have suggested that people with HIV appear to be at lower risk of hypertension than matched HIV uninfected counterparts 13-16 . Given that we did not have an HIV-uninfected comparison group in our study, we cannot rule out the possibility that blood pressure remains lower in the HIV-infected population despite the increases we documented.…”
Section: Discussionmentioning
confidence: 44%
“…While a number of studies have reported high incidence rates 8-12 , others suggest that people with HIV are at lower risk of hypertension than matched HIV uninfected counterparts 13-16 . However, these studies are confounded by the inconsistent inclusion of patients with and without AIDS as well as the variable use and duration of ART in the cohorts 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Cross‐sectional studies report a wide range of effects of HIV and antiretroviral therapy (ART) on blood pressure (BP), with literature comparing estimates between HIV‐infected individuals to HIV‐uninfected individuals reporting higher BP, similar BP, and lower BP . The later studies were conducted in sub‐Saharan Africa (SSA), where concomitant comorbidities for people living with HIV (PLWH) differ from those in high‐income countries, and where the disparity in access to care for people with HIV in contrast to uninfected people may be different than in high‐income countries …”
Section: Introductionmentioning
confidence: 99%